Treatment outcomes in patients with multidrug‐resistant tuberculosis in north‐west Ethiopia. Issue 3 (6th January 2017) - Alene, Kefyalew Addis; Viney, Kerri; McBryde, Emma S.; Tsegaye, Adino Tesfahun; Clements, Archie C. A.
Abstract: Objective: Multidrug‐resistant tuberculosis (MDR‐TB) is an emerging public health problem in Ethiopia. The aim of this study was to assess MDR‐TB treatment outcomes and determine predictors of poor treatment outcomes in north‐west Ethiopia. Methods: A retrospective cohort study was conducted using all MDR‐TB patients who were enrolled at Gondar University Hospital since the establishment of the MDR‐TB programme in 2010. A Cox proportional hazard model was used to identify the predictors of time to poor treatment outcomes, which were defined as death or treatment failure. Results: Of the 242 patients who had complete records, 131 (54%) were cured, 23 (9%) completed treatment, 31 (13%) died, four (2%) experienced treatment failure, 27 (11%) were lost to follow‐up, six (2%) transferred out, and 20 (8%) were still on treatment at the time of analysis. The overall cumulative probability survival of the patients at the end of treatment (which was 24 months in duration) was 80% (95% CI: 70%, 87%). The proportion of patients with poor treatment outcomes increased over time from 6% per person‐year (PY) during 2010–2012, to 12% per PY during 2013–2015. The independent predictors of time to poor treatment outcome were being anaemic [AHR = 4.2; 95% CI: 1.1, 15.9] and being a farmer [AHR = 2.2; 95% CI: 1.0, 4.9]. Conclusions: Overall, in north‐west Ethiopia, the MDR‐TB treatment success rate was high. However, poor treatment outcomes have gradually increased since 2012. Being a farmer and being anaemic were associated with poor treatment outcomes. It would be beneficial to assess other risk factors that might affect treatment outcomes such as co‐infection with malaria, poverty and other socio‐economic and biological risk factors.